Yield of tuberculosis screening in asylum-seekers by country of origin: analysis of screening data in a German federal state (2002-2015) - Bozorgmehr, Kayvan; Stock, Christian (The European respiratory journal, 2017)
Tweetable abstract ERSpublications click to tweet Yield of TB screening varies by country of origin; targeted approaches are needed to increase screening efficiency http://ow.ly/SuvZ30941Ej